The Role of Vocational School Students' Entrepreneurship Practices in Sharia Economic Studies in Forming Entrepreneurial Interest and Competence - Dede Munawar; Wawan Kurniawan; Udin Wahrudin (International Journal of Economics, Management and Accounting (IJEMA), 2023)
The background to this research is the importance of entrepreneurship education given to the younger generation through formal education, so that they can build independence and improve their welfare. Many people believe that to build entrepreneurship, a person must have talent and skills, so that not all individuals can be involved in entrepreneurial activities. The aim of this research is to determine the role of vocational school students' entrepreneurial practices in sharia economic studies in forming entrepreneurial interests and competencies. The method used in this research is qualitative. The results of this research indicate that a) Entrepreneurship education can have a positive impact in forming entrepreneurial interest, b) Entrepreneurship education programs provide opportunities for individuals to develop management, leadership, innovation, problem solving, communication and financial skills needed in the business world, c ) Through learning and interaction with business practitioners, individuals can develop attitudes such as self-confidence, independence, resilience, and orientation towards achieving relevant goals in an entrepreneurial context, as well as d) Through entrepreneurship education programs, individuals can gain better access to resources and business networks, including mentors, potential business partners, and financial institutions.